Microfinancing and Entrepreneurial Processes Among Females: A Role Congruity Theory Perspective - Farzana, Riaheen; Karau, Steven J. (American Journal of Management, 2023)
This research qualitatively investigates the activities that female entrepreneurs perform to become successful in their ventures with the support of microfinancing. Based on interviews with 34 female entrepreneurs from five regions of Bangladesh, this study sought to identify significant categories of start-up companies related to the development of entrepreneurship among rural women borrowers through microfinancing. Specifically, this study examined obstacles faced by females of Bangladesh and explored how they overcame those barriers and became successful entrepreneurs. A grounded theory approach was used to categorize critical obstructions and facilitating factors, and role congruity theory helped inform the nature of the emerging categories. Nine compelling themes emerged from the analysis, identifying vital factors influencing the nature and outcome of the small business ventures. From a role congruity theory perspective, the nine themes converge to suggests that microfinancing allows women to operate their businesses in a manner that enables them to maintain high congruity or fit with their family roles and other lifestyle requirements, contributing to successful business operations.